THE IMPACT OF CONSUMER REVIEWS ON INTEREST AND PURCHASING POWER FOR L'ORÉAL PARIS BEAUTY PRODUCTS - Siwi Putri Andini; Miranti Andhita Scantya; Antonius Juniarto; Yandri Ardolof Toar (Journal of Innovation Research and Knowledge, 2025)
This research aims to analyze the impact of consumer reviews as digital marketing for purchasing intention and purchasing power of the product. This research employs a descriptive quantitative method, involving 30 respondents who were given information about the product through video reviews made by an influencer and reviews written by product buyers. Descriptive quantitative research is used as an approach to describe a phe nomenon of product reviews systematically and objectively by relying on numerical data collected through a structured questionnaire distributed to respondents. The data processed by SPSS, the statistical software used to help with structured observations. The results showed a significant relationship between consumer reviews and product purchase intention, with a calculated Z-value of -3.81. Since the Z-value fell within the rejection region (less than the critical value of -1.645 for a one-tailed test at a 95% confidence level), it meant the null hypothesis is false and it concluded there was a relationship between consumer reviews and purchase intention, and the relationship between these variables are statistically significant. This indicated that positive reviews can increase consumer trust and strengthen purchase decisions. The results can be used for Further research, including optimizing digital marketing strategies through consumer reviews, increasing brand engagement with customers, and strengthening testimonial-based marketing communication strategies